Judicial Construction of Tadlis in Marriage Annulment Litigation: Comparative Ushul Fiqh Examination of Decision No. 2309/Pdt.G/2025/PA.Krs - Syafariah Karomah; Vita Firdausiyah; Ramdan Wagianto (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2026)
This study examines how judges assess the validity of tadlis claims in marriage annulment cases and evaluates whether their judicial reasoning aligns with comparative ushul fiqh principles. The issue has become increasingly significant in contemporary Islamic family law due to the growing number of cases involving identity fraud, concealment of material facts, and misrepresentation that potentially affect the validity of marriage contracts. Employing a normative-analytical legal research approach, this study integrates judicial reasoning analysis with comparative ushul fiqh perspectives through the bayani (textual), ta’lili (causal), and maqasidi (objectives-oriented) methods. The primary sources consist of judicial decisions, statutory regulations, and classical as well as contemporary fiqh literature relevant to the doctrine of tadlis and marriage annulment. The findings indicate that judges do not rely solely on formal evidentiary standards but also consider substantive facts, contextual legal interpretation, and principles of material justice in determining the validity of tadlis claims. From a comparative ushul fiqh perspective, judicial reasoning demonstrates a balanced integration of textual evidence, legal causation (‘illat), and the objectives of Islamic law (maqasid al-shari‘ah), particularly in protecting honesty, legal certainty, and family welfare. This study contributes to Islamic family law scholarship by illustrating how judicial discretion functions as a bridge between positive law and Islamic legal principles in achieving both legal certainty and substantive justice in marriage annulment disputes.